ANALISIS IMPLEMENTASI PENGANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS PEMERINTAH DAERAH (Studi pada Instansi Pemerintah Daerah) - Syamsul, Endang Mahpudin Made Panji (Program Studi Akuntansi, Universitas Kuningan, 2017)
The implementation of good governance is a prerequisite condition for every government to achieve people's aspirations. Every work unit is determined to reach agency accountability as the consequence of the mandate/responsibility it carries. This is done through considering the resources it manages in order to make government and development run effectively and efficiently, clean and responsibly.Â The research aims to find out and analyze the influence of performance-based budgeting performance on the accountability of government agencies within Karawang Regency. This research uses descriptive quantitative method in the form of statistical analysis, where the data is sourced from primary and secondary data coming from local government of Karawang Regency or other institutions related to this research. Descriptive method is a method that describes and presents an object as it is. Quantitative analysis in research design is intended to know the influence between independent variables with dependent variable. Based on the results of analysis and discussion, a conclusion can be drawn, that the implementation of performance-based budgeting affects the accountability of local government agencies within Karawang Regency. Improved implementation of performance-based budgeting will be followed by increased accountability of local government agencies. Â Keywords:Â Performance-based Budgeting, Accountability, Local Government